2023
DOI: 10.1038/s41598-023-32717-y
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA sequencing of circulating small extracellular vesicles microRNAs in patients with amyotrophic lateral sclerosis

Abstract: Dysregulation of microRNAs (miRNA) in small extracellular vesicles (sEV) such as exosomes have been implicated in the pathogenesis of amyotrophic lateral sclerosis (ALS). Although circulating cell-free miRNA have been extensively investigated in ALS, sEV-derived miRNAs have not been systemically explored yet. Here, we performed small RNA sequencing analysis of serum sEV and identified 5 differentially expressed miRNA in a discovery cohort of 12 patients and 11 age- and sex-matched healthy controls (fold change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This dysregulation associated with neurodegeneration causing ALS could pave the way for the identification of potential biomarkers of the disease [ 187 ]. Similarly, Kim et al [ 188 ] studied small RNA sequencing of 18 ALS patients and 15 healthy individuals. It was found that five of the miRNAs are differentially expressed in the patients of ALS as compared to the healthy individuals.…”
Section: Applications Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…This dysregulation associated with neurodegeneration causing ALS could pave the way for the identification of potential biomarkers of the disease [ 187 ]. Similarly, Kim et al [ 188 ] studied small RNA sequencing of 18 ALS patients and 15 healthy individuals. It was found that five of the miRNAs are differentially expressed in the patients of ALS as compared to the healthy individuals.…”
Section: Applications Of Exosomesmentioning
confidence: 99%
“…Bioinformatic analysis revealed that these miRNAs interact with different sets of genes which are involved in pathogenies in ALS. So, these two miRNAs can serve as potential biomarkers for detecting ALS [ 188 ]. In another study by Saucier et al [ 189 ], it was found that miR-15a-5p could serve as a biomarker for the diagnosis of ALS, as miR-193a-5p is linked to the progression of ALS.…”
Section: Applications Of Exosomesmentioning
confidence: 99%
“…This investigation showed a positive and negative regulation of miR-23c and miR-192-5p, respectively, in patients with ALS. The analysis of bioinformatics revealed that these miRNAs interact with different target genes and are involved in the biological processes of ALS [129]. Regarding Alzheimer's disease, miR-146a is constantly investigated.…”
Section: Mirnas In Neurodegenerative Diseases and Association With He...mentioning
confidence: 99%